1998
DOI: 10.1111/j.1469-7998.1998.tb00042.x
|View full text |Cite
|
Sign up to set email alerts
|

An example of segregation between age and sex classes only weakly related to habitat use in mouflon sheep (Ovis gmelini)

Abstract: Sexual segregation reported in many wild ruminants is generally assumed to result from either different habitat choices by adult males and females or`social factors'. In this framework, we studied group composition and habitat use of mou¯on sheep (Ovis gmelini) over an annual cycle in the low-mountain range of Caroux-Espinouse (continental France). The analysis of group composition revealed segregation outside the rut, not only between the sexes, but also between the young (2±3 years) and old rams (! 4 years).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 34 publications
(48 reference statements)
1
37
0
1
Order By: Relevance
“…Therefore the sexual-segregation peak we observed in spring in both populations (figure 2) cannot be accounted for by sexual differences in forage selection or activity budget caused by lactation alone, and is likely to be related to the antipredator behaviour. (c) Social segregation Sexual segregation was long thought to be a by-product of different habitat selection by females and males (Clutton-Brock et al 1987), even though some studies reported segregation despite small differences in habitat use between the sexes (Cransac et al 1998;Ruckstuhl 1998). Sexual segregation regardless of habitat (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the sexual-segregation peak we observed in spring in both populations (figure 2) cannot be accounted for by sexual differences in forage selection or activity budget caused by lactation alone, and is likely to be related to the antipredator behaviour. (c) Social segregation Sexual segregation was long thought to be a by-product of different habitat selection by females and males (Clutton-Brock et al 1987), even though some studies reported segregation despite small differences in habitat use between the sexes (Cransac et al 1998;Ruckstuhl 1998). Sexual segregation regardless of habitat (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies dealing with sexual segregation have considered data from all seasons (e.g. Miquelle et al 1992;Villaret et al 1997;Cransac et al 1998;Bon et al 2001), but all except Cransac et al (1998), who presented monthly estimates for mouflon sheep (Ovis gmelini ), provided the segregation estimates on a coarse time-scale. High-resolution temporal patterns of sexual segregation covering the full year have therefore rarely been presented for ungulates, and previous studies have never taken advantage of methodological improvements that allow separation of the social and habitat components of segregation (Conradt 1998b).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature (daily mean) and the date of surveys ranged from 6.3°C to 20.3°C and from 13 May to 14 June, respectively, for the pedestrian surveys, and from 11.0°C to 23.0°C and from 5 June to 12 July, respectively, for the helicopter surveys. The date of survey and the temperature are expected to influence counts because these variables influence the use of open areas by mouflons and the intensity of spatial and sexual segregation (Bon et al 1990;Santosa et al 1990;Cransac et al 1998). We also accounted for differences in PAI and in temperature according to transects due to differences in space use of mouflons and physical characteristics of the sample areas (e.g.…”
Section: Model Adjustmentmentioning
confidence: 99%
“…Studies of several ungulate species (Cransac et al 1998;Conradt 1999;Bon et al 2001;Bonenfant et al 2004) have consistently reported higher degrees of social than habitat segregation, suggesting that if environmental factors are involved, they are insufficient to explain the low occurrence of mixed-sex groups in wild populations. This has led to other hypotheses based on non-ecological mechanisms being proposed -in particular, the social affinity and activity budget hypotheses, both of which focus more specifically on the mechanisms involved in group formation and cohesion.…”
Section: Introductionmentioning
confidence: 96%